Dose-dependent immunotoxic mechanisms of celastrol via modulation of the PI3K-Akt signaling pathway - Geng, Shaohui; Wen, Jingqi; Shen, Chunli; Liu, Li; Jiang, Yijin; Fu, Jingyuan; Guan, Yiwei; Ye, Zi; Wu, Yuanhao; Li, Chen; Huang, Guangrui (Frontiers in Pharmacology, 2025)
Ethnopharmacological relevanceCelastrol, a bioactive compound from Tripterygium wilfordii Hook.f., is known for its anti-inflammatory and immunomodulatory effects, but its immunotoxicity is underexplored. This study investigates the mechanisms of celastrol-induced immunotoxicity, focusing on the PI3K-Akt signaling pathway, a key regulator of immune function.Materials and methodsAn integrative approach combining network toxicology, molecular docking, and experimental biology identified molecular targets in celastrol-induced immune dysfunction. Network toxicology mapped key pathways, and molecular docking predicted interactions with immune-related proteins. High-dose celastrol (10 mg/kg) was administered to C57BL/6J mice, followed by a histopathological analysis of the thymus and spleen. RNA-Seq evaluated gene expression in immune pathways, and IHC/mIHC validated PI3K-Akt signaling pathway protein expression.ResultsNetwork toxicology identified the PI3K-Akt signaling pathway as a key target of celastrol’s immunotoxic effects. High-dose celastrol caused histopathological damage in the thymus and spleen, including lymphocyte depletion and immune cell infiltration. RNA-Seq showed upregulation of critical genes in the PI3K-Akt signaling pathway (Egfr, Pik3c, Akt3), linked to cell proliferation and survival. IHC confirmed increased expression of EGFR, AKT, PIK3, and mTOR, with decreased PTEN. mIHC revealed elevated macrophage activation and inflammation. In contrast, low-dose celastrol suppressed PI3K-Akt signaling by downregulating mTOR, indicating dose-dependent modulation of immune function.ConclusionOur study demonstrates the dose-dependent immunotoxic effects of celastrol, which is toxic in high doses caused by activation of the PI3K-Akt signaling pathway, while low doses offer protection by blocking this signaling pathway. These findings emphasize the importance of dose selection in therapeutic and safety contexts, enhancing understanding of celastrol’s biological effects and its clinical potential in immune-related diseases.